Unraveling molecular interconnections and identifying potential therapeutic targets of significance in obesity-cancer link - Alanoud Abdulla; Hana Q. Sadida; Jayakumar Jerobin; Imadeldin Elfaki; Rashid Mir; Sameer Mirza; Mayank Singh; Muzafar A. Macha; Shahab Uddin; Khalid Fakhro; Ajaz A. Bhat; Ammira S. Al-Shabeeb Akil (Journal of the National Cancer Center)
Obesity, a global health concern, is associated with severe health issues like type 2 diabetes, heart disease, and respiratory complications. It also increases the risk of various cancers, including melanoma, endometrial, prostate, pancreatic, esophageal adenocarcinoma, colorectal carcinoma, renal adenocarcinoma, and pre-and post-menopausal breast cancer. Obesity-induced cellular changes, such as impaired CD8+ T cell function, dyslipidemia, hypercholesterolemia, insulin resistance, mild hyperglycemia, and fluctuating levels of leptin, resistin, adiponectin, and IL-6, contribute to cancer development by promoting inflammation and creating a tumor-promoting microenvironment rich in adipocytes. Adipocytes release leptin, a pro-inflammatory substance that stimulates cancer cell proliferation, inflammation, and invasion, altering the tumor cell metabolic pathway. Adiponectin, an insulin-sensitizing adipokine, is typically downregulated in obese individuals. It has antiproliferative, proapoptotic, and antiangiogenic properties, making it a potential cancer treatment. This narrative review offers a comprehensive examination of the molecular interconnections between obesity and cancer, drawing on an extensive, though non-systematic, survey of the recent literature. This approach allows us to integrate and synthesize findings from various studies, offering a cohesive perspective on emerging themes and potential therapeutic targets. The review explores the metabolic disturbances, cellular alterations, inflammatory responses, and shifts in the tumor microenvironment that contribute to the obesity-cancer link. Finally, it discusses potential therapeutic strategies aimed at disrupting these connections, offering valuable insights into future research directions and the development of targeted interventions.